2020
DOI: 10.3168/jds.2019-17726
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the skim milk and milk fat globule membrane proteomes produced by Jersey cows grazing pastures with different plant species diversity

Abstract: The objective of this experiment was to identify and characterize the bovine milk proteome within the skim milk fraction and milk fat globule membrane (MFGM)-associated fraction from 16 organically certified lactating Jersey cows after a short term of grazing pastures with or without annual forage crops (AFC). Cows were offered a partial mixed ration (~60% of dry matter intake) and approximately 40% of their total dry matter intake as herbage. Eight cows were offered a cool-season grass–legume herbage (GLH), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…El nivel de proteína en leche varió significativamente entre plantas (p<0.05), presentando mayores niveles la planta 8 y niveles bajos las plantas 1 y 10 (Tabla 2). Los valores de proteína de este estudio son similares al 3.43% (vacas que pastorearon un pasto leguminoso) y 3.72% vacas alimentadas con cultivos anuales) ( y están dentro del Scuderi et al, 2020) rango estándar de proteína de 3.9% hasta 3.9% (Gómez y Mejía, 2005).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El nivel de proteína en leche varió significativamente entre plantas (p<0.05), presentando mayores niveles la planta 8 y niveles bajos las plantas 1 y 10 (Tabla 2). Los valores de proteína de este estudio son similares al 3.43% (vacas que pastorearon un pasto leguminoso) y 3.72% vacas alimentadas con cultivos anuales) ( y están dentro del Scuderi et al, 2020) rango estándar de proteína de 3.9% hasta 3.9% (Gómez y Mejía, 2005).…”
Section: Discussionunclassified
“…La membrana del glóbulo graso de la leche es integral y se correlaciona con la secreción de grasa láctea; por tanto, es factible que los aumentos en la producción de grasa de la leche aumenten la abundancia de proteínas y péptidos bioactivos en la leche ( . Scuderi et al, 2020) Un estudio demostró que, las propiedades de coagulación de la leche favorables se asocian con un pH bajo (0,52 y −0,43 para tiempo de coagulación y firmeza de la cuajada, respectivamente) y una alta acidez (−0,46 y 0,41 para tiempo de coagulación y firmeza de la cuajada, respectivamente) (Cassandro et al, 2008). Este tipo de asociación también fue informado por Ikonen et al (2004) para el rasgo de pH.…”
Section: Discussionunclassified
“…Cui et al confirmed that tartary buckwheat could alleviate rumen methane emissions by improving the morphology of gut microbes [21]. Scuderi et al reported that adding buckwheat ingredients to forage could effectively improve the morphology of intestinal microbes in ruminant animals by affecting the fermentation activity of ruminant rumen microbes [22]. Amelchanka et al also found that addition of a proper amount of buckwheat to forage could improve the palatability and productivity of dairy cows [23].…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of animal husbandry breeding technology, the planting area of grass forages is also expanding, especially for alfalfa and oat. Oat forage has high nutritional value with high protein and fat content, whose Lysine content is more than twice that of corn [3,4]. At the same time, alfalfa, which enjoys the reputation of being the "king of pasture," has become a reliable plant-based protein feed source due to its rich nutrition, strong adaptability, good palatability, and easy digestion by livestock [5,6] .…”
Section: Introductionmentioning
confidence: 99%